Effect of a tailored home‐based exercise program in patients with systemic sclerosis: A randomized controlled trial. (11th May 2020) - Filippetti, Mirko; Cazzoletti, Lucia; Zamboni, Francesco; Ferrari, Pietro; Caimmi, Cristian; Smania, Nicola; Tardivo, Stefano; Ferrari, Marcello
Abstract : Objective: The aim was to evaluate the effect of a home‐based exercise program on functional capacity, health‐related quality of life (HRQoL), and disability, in patients with systemic sclerosis (SSc). Methods: A 6‐month randomized controlled trial was conducted on SSc patients by comparing a home‐based minimally supervised exercise program (exercise on a stationary cycle and strengthening of upper limbs; stretching of the hands) with usual care. At baseline and after 3 and 6 months, the patients underwent: 6 minutes walking test; hand mobility in scleroderma test; maximal exercise test on an ergocycle; strength measures (handgrip, quadriceps, and biceps). HRQoL (short‐form 36 [SF‐36]) and disability (health assessment questionnaire disability index [HAQ‐DI]) were measured at the same time. Results: Forty‐four patients participated in the study. Twenty‐two were randomly assigned to the intervention group (IG, mean age 63.60 ± 10.40 years) and 22 to the control group (CG, 61.80 ± 14.40 years). At 6 months, the distance walked in 6 minutes increased by 46 m (baseline 486, 95% CI 458‐513 m; 6 months 532, 95% CI 504‐561 m) in IG, whereas it decreased by 5 m (baseline 464, 95% CI 431‐497 m; 6 months 459, 95% CI 427‐490 m) in CG with a significantly different temporal trend at the between‐groups comparison ( P < .001). An improvement was also observed for strength measures (handgrip, P = .003; quadriceps, P < .001; biceps, P < .001), for the SF‐36 physical component score ( P < .001) and for the HAQ‐DI ( P = .011). Conclusions: This study indicates that in SSc patients, a minimally supervised home‐based exercise program improves physical performance, quality of life, and disability in comparison with usual care.